Biomass of a fragment of the montane seasonal deciduous forest the south Brazil - Balbinot, Rafaelo; Trautenmuller, Jonathan William; Lambrecht, Fernanda Raquel; Breunig, Fábio Marcelo; Valerius, Jaqueline (Acta Iguazu, 2019)
The objective the work was to quantify the biomass using the destructive method of a forest fragment located in the South of Brazil. The study was conducted in fragment of Montane Seasonal Deciduous Forest with approximately 55 ha, centered at the coordinates S 27˚23’44” and W 53˚25’59”. For that, three plots of 12x12 m were installed. All plants with diameter at breast height (DBH) greater than 5 cm were identified at the species level. All trees with DBH>10 cm had the following information collected: DBH, total height (h), height at the morphological inversion point (MIP) and the diameter at 0%, 25%, 50%, 75% and 90% of the MIP height. As result, we verified that trees with DBH> 10 cm represent more than 90% of the total biomass (345.2 Mg ha-1). The estimated biomass of leaf litter was 12.4 Mg ha-1. The stock of dry aboveground biomass and litter for the study area was 380.5 Mg ha-1.